Investigating the antecedents of Enterprise Content Management System (ECMS) benefits / Mohamad Rahimi Mohamad Rosman, Mohammad Azhan Abdul Aziz and Mohd Idzwan Mohd Salleh - Mohamad Rosman, Mohamad Rahimi; Abdul Aziz, Mohammad Azhan; Mohd Salleh, Mohd Idzwan (2018)
Enterprise Content Management System (ECMS) was introduced to help organizations manage their contents. In current business environment, possessing large chunks of unstructured contents prevents organizations from achieving benefits from the use of an Information System (IS). Although beneficial, the voices from academics and practitioners seem contradicting with ECMS vendors; particularly relating to benefits achievement. Therefore, the purpose of this study is to investigate the antecedents driving the achievement of ECMS benefits. Grounded on the literature of ECMS and Enterprise Resource Planning (ERP), several antecedents are identified. These antecedents are categorized into three categories; technological, organizational, and environmental. Subsequently, potential research gaps were identified and future works are outlined.